Tópicos em teoria das perturbações cosmológicas - Santos, Renato da Costa [UNESP] (2016)
In this thesis the Theory of Cosmological Perturbations is reviewed and three original topics, that are part of this huge branch of theoretical cosmology, are presented. We start by reviewing and deducing the needed formulas from first principles in chapter 2. After it, in chapter 3, we study in detail Quantum Field Theories in de Sitter spacetime that contain Higher Spin currents. We show that the existence of Higher Spin currents - even in the interacting case - can put further constraints on the n-point function, making it asymptotically gaussian in the far future. This result can be interpreted as the analog of Coleman-Mandula theorem for de Sitter spacetime. Chapter 4 is devoted to conformal inflationary models with the Higgs field playing the role of the Inflaton field. We construct models with a Weyl symmetry and a SO(1, 1) symmetry at high energies. It is verified what are the conditions to get an arbitrary value for the tensor to scalar ratio, which measures the amplitude of primordial gravitational waves in a given model. Also, we introduce a coupling, different from the conformal one, for the scalar field and the curvature tensor. This breaks the Weyl symmetry but we verify that there is a strong attractor towards the Starobinsky line. In the last chapter, we apply the back-reaction effect of long wavelength modes (modes with wavelength bigger than the Hubble radius) in some inflationary models and in the Ekpyrotic scenario. We check if this effect could prevent eternal inflation in the region where stochastic effects are important for these models. Some appendices, with detailed calculations, are also included in the end.